2014
DOI: 10.3390/ijms15045762
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Elongation in Non-Alcoholic Steatohepatitis and Hepatocellular Carcinoma

Abstract: Non-alcoholic steatohepatitis (NASH) represents a risk factor for the development of hepatocellular carcinoma (HCC) and is characterized by quantitative and qualitative changes in hepatic lipids. Since elongation of fatty acids from C16 to C18 has recently been reported to promote both hepatic lipid accumulation and inflammation we aimed to investigate whether a frequently used mouse NASH model reflects this clinically relevant feature and whether C16 to C18 elongation can be observed in HCC development. Feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 46 publications
5
49
0
Order By: Relevance
“…The present study used FFAs to establish a cell model of human NAFLD. The results showed triglyceride accumulation in HepG2 cells after treatment with FFAs, consistent with previous studies [27][28][29][30].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The present study used FFAs to establish a cell model of human NAFLD. The results showed triglyceride accumulation in HepG2 cells after treatment with FFAs, consistent with previous studies [27][28][29][30].…”
Section: Discussionsupporting
confidence: 81%
“…When obesity causes triglycerides failure to be stored in the adipose tissue, triglycerides are transformed into FFAs that are transported to nonadipose tissues [26]. Saturated palmitic (PA; C16:0) and monounsaturated oleic (OA; C18:1) acids are the most abundant FFAs in the liver triglycerides of patients with NAFLD [27,28]. Previous studies showed that in vitro NAFLD models induced by FFAs mixture (PA/OA, 1:2 ratio) could lead to triglyceride accumulation in hepatocytes similar to that of patients with NAFLD, with minor toxic and apoptotic effects [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acid composition and the accumulation of free cholesterol have been implicated in playing a critical role in the development of NASH since an altered lipidome [3,11,12] as well as free cholesterol, positively correlate with the severity of NASH [10,12,28,29] . Dietary cholesterol may play a role in NAFLD onset [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid extraction and alkaline hydrolysis was performed using the fatty acid methyl ester method and measured with GC-MS as previously published [3,23] .…”
Section: Fatty Acid Profile Analysismentioning
confidence: 99%
See 1 more Smart Citation